Peculiarities of isolation and identification of infections rhinitis in chickens (coryza) - V. A. Danilova; A. V. Potekhin; I. A. Stepanova (Ветеринария сегодня)
Pathological material from poultry was subjected to bacteriological tests for infectious rhinitis in chickens. Nine Avibacteruim paragallinarum isolates were recovered from 84 samples, i.e. 10.7%. The agent was recovered from mucosal exudate of nasal cavity and infraorbital sinuses, from conjunctival sac content and lungs. All the isolates were gram-negative short rods or Cocci that needed V-growth factor and sera, did not produce catalase, fermented glucose and sucrose, did not split trehalose and galactose. Taking into account the mentioned signs, it was possible to differentiate Avibacteruim paragallinarum from other apathogenic avian heamophilius bacteria.